Workshop Review: New Economic Sociology and Sociology: Where Do They Meet? Where Do They Diverge? Warsaw, May 22–23, 2017 - Mica, Adriana; Olcon´-KubickaMarta; WyrzykowskaKatarzyna M. (Journal of Economic Sociology, 2017)
This review presents the theoretical grounding and agenda of a series of works on new economic sociology that was launched in May 2017, in Warsaw, by the Polish Sociological Association’s recently constituted Economic Sociology Section. The workshop series comprises three annual meetings held in the second part of May. The long-term plan is to explore the relationship between sociology and new economic sociology by considering specific theoretical problems and, eventually, research sites. The first meeting, which was held this year, was a general warm-up and an attempt to establish the nature of the borders between new economic sociology and the discipline of sociology, and, to a certain extent, even economics. The second meeting, scheduled for 2018, aims to investigate the modalities of reacting to organizational decline or economic crises that the new economic sociology may be considered to have highlighted in addition to Albert O. Hirschman’s “Exit, Voice, and Loyalty.” The third meeting, which will take place in 2019, is planned in relation to a concrete research site that has been explored in new economic sociology, sociology, and anthropology (e.g., consumption; economic practices concerned with work, entrepreneurship, health, and education; or even art and food).